2021
DOI: 10.1021/acs.est.1c02630
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Removal of Trace 17β-Estradiol and Estrogenic Activity in Blended Systems under a Photoelectrocatalytic Circulating Flow

Abstract: Trace 17β-estradiol (E2) is persistent against advanced treatment when blended with higher concentrations of low-toxicity organics, thus wasting energy. A circulating-flow selective photoelectrocatalysis (CF-SPEC) system is established with a selective E2-TiO2-NR photoanode, accurately reducing 1 μg L–1 E2 to less than 0.1 ng L–1 along with eliminating estrogenic activity even when blended with natural organic matter (NOM) at a thousand times higher concentration. Such high efficiency is derived from the augme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Not only can it provide reliable maximum adsorption capacity data, but it is also more favorable for the study of coadsorption, competitive adsorption, and displacement adsorption. It was recently applied to probe the competitive adsorption of 17β-estradiol and NOM on molecularly imprinted TiO 2 anodes, guiding the selective elimination of estrogen activity under rapid-flow conditions . The breakthrough curve reflects the adsorption equilibrium relationship, adsorption kinetics, and mass transfer mechanism between the mobile phase adsorbate and stationary phase adsorbent.…”
Section: Advanced Measurement and Characterization Methods In Selecti...mentioning
confidence: 99%
See 2 more Smart Citations
“…Not only can it provide reliable maximum adsorption capacity data, but it is also more favorable for the study of coadsorption, competitive adsorption, and displacement adsorption. It was recently applied to probe the competitive adsorption of 17β-estradiol and NOM on molecularly imprinted TiO 2 anodes, guiding the selective elimination of estrogen activity under rapid-flow conditions . The breakthrough curve reflects the adsorption equilibrium relationship, adsorption kinetics, and mass transfer mechanism between the mobile phase adsorbate and stationary phase adsorbent.…”
Section: Advanced Measurement and Characterization Methods In Selecti...mentioning
confidence: 99%
“…(D) enhanced recognition capacity in a circulating flow system, CE = counter electrode. Adapted with permission from ref . Copyright 2021 American Chemical Society.…”
Section: Approaches Of Achieving Selectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…This result shows that selective PEC can reduce the energy cost. In addition, preferential removal of 17β-estradiol can be completed in a circulating flow PEC system . It has been shown that initial hydroxyl radical production greatly increases under flow conditions in a self-designed electron paramagnetic resonance (EPR) device (Figure d).…”
Section: State Of the Art Of Photoelectrocatalysis For Environmental ...mentioning
confidence: 99%
“…(e) Scheme of an integrated medical wastewater treatment system. Reproduced with permission from ref . Copyright 2021 American Chemical Society.…”
Section: State Of the Art Of Photoelectrocatalysis For Environmental ...mentioning
confidence: 99%